The Rice Abscisic Acid-Responsive RING Finger E3 Ligase OsRF1 Targets OsPP2C09 for Degradation and Confers Drought and Salinity Tolerance in Rice - Kim, Suyeon; Park, Seong-Im; Kwon, Hyeokjin; Cho, Mi Hyeon; Kim, Beom-Gi; Chung, Joo Hee; Nam, Myung Hee; Song, Ji Sun; Kim, Kyung-Hwan; Yoon, In Sun (Frontiers in Plant Science, 2022)
Drought and salinity are major important factors restrain growth and productivity of rice. In plants, many RING (Really Interesting New Gene) finger proteins has been reported to enhance drought and salt tolerance. However, their mode of action and interacting substrates are largely unknown. Here, we identified a new small RING-H2 type E3 ligase OsRF1 which is involved in the ABA and stress responses of rice. The OsRF1 transcripts were highly induced by ABA, salt or drought treatment. Upregulation of OsRF1 in transgenic rice conferred drought and salt tolerance and increased endogenous ABA levels. Consistence with this, faster transcriptional activation of key ABA biosynthetic genes, ZEP, NCED3 and ABA4, was observed in the OsRF1-OE plants compared with wild type in response to drought stress. Yeast two-hybrid assay and BiFC analysis identified clade A PP2C proteins as direct interacting partners with OsRF1. In vitro ubiquitination assay indicated that OsRF1 exhibited E3 ligase activity and targets OsPP2C09 protein for ubiquitination and degradation. Cell free degradation assay further showed that the OsPP2C09 protein is more rapidly degraded by ABA in the OsRF1-OE rice than in the wild type. The combined results suggested that OsRF1 is a positive player of stress responses by modulating protein stability of clade A PP2C proteins, the negative regulators of ABA signaling.